Resensitization in suspected penicillin allergy - Doña, Inmaculada; Guidolin, Lucia; Bogas Herrera, Gádor; Olivieri, Elisa; Labella, Marina; Schiapolli, Michele; Saenz de Santa María-García, Rocío; Dama, Annarita; Salas, María; Senna, Gianenrico; Bonadonna, Patrizia; Torres-Jaén, María Josefa (Wiley, 2022)
The diagnosis of allergic reactions to penicillins (AR-PEN) is very complex as there is a loss of sensitization over time, which leads to negative skin tests (STs) and specific IgE in serum, and even to tolerance to the drug involved. However, STs may become positive after subsequent exposure to the culprit drug (resensitization), with the risk of inducing potentially severe reactions. The exact rate of resensitization to penicillins is unknown, ranging from 0% to 27.9% in published studies. Objectives To analyze the rate of resensitization in patients with suggestive AR-PEN by repeating STs (retest) after an initial evaluation (IE). Material and Methods Patients with suspected AR-PEN were prospectively evaluated between 2017 and 2020. They underwent STs, and a randomized group also underwent a drug provocation test (DPT) with the culprit. Only patients with negative STs and/or DPT were included. All included cases were retested by STs at 2–8 weeks. Results A total of 545 patients were included: 296 reporting immediate reactions (IRs) and 249 non-immediate reactions (NIRs). Eighty (14.7%) cases had positive results in retest (RT+): 63 (21.3%) IRs and 17 (6.8%) NIRs (p < 0.0001). The rate of RT+ was higher in anaphylaxis compared with all other reactions (45.8% vs 9.1%, p < 0.0001). The risk of RT+ was higher from the fifth week after IE (OR: 4.64, CI: 2.1–11.6; p < 0.001) and increased with the patient's age (OR: 1.02; CI: 1.01–1.04; p = 0.009). Conclusions Due to the high rate of resensitization, retest should be included in the diagnostic algorithm of IRs to penicillins after an initial negative study, especially in anaphylaxis, to avoid potentially severe reactions after subsequent prescriptions of these drugs.
Keywords: Anafilaxia; Anaphylaxis; Drug provocation test; Penicillins; Resensitization; Skin test; Specific IgE